Etiology and prevention of noncontact ACL injury - Boden, B. P.; Griffin, L. Y.; Garrett, W. E. (The Physician and Sportsmedicine, 2000)
An understanding of the etiology and prevention of noncontact ACL injuries has lagged behind diagnosis and treatment. However, a growing research implicates hormonal, anatomic, environmental, and neuromuscular factors that may predispose athletes, particularly women, to these injuries. Specific factors may include estrogen levels, the shape of the intercondylar notch, playing style, and neuromuscular control of the quadriceps and hamstring muscles. Prevention programs that involve proprioception, plyometrics, strength training, and improved jumping, stopping, and turning techniques show promising results.